Unveiling the Subtle Distinctions Between Adapt, Adjust, and Modify: A Corpus-Based Analysis of English Synonyms - Julul, Ali; Al-Marrani, Yahya (International Journal of Language and Literary Studies, 2026)
This study investigates the similarities and, more importantly, the differences among the English synonymous verbs, namely adapt, adjust, and modify in terms of their collocations and semantic preferences. Despite being presented in major dictionaries as synonyms, these verbs exhibit subtle distinctions that lead to confusion among EFL learners. The data were drawn from the Corpus of Contemporary American English (2020). Additionally, this research employed quantitative and qualitative corpus-based method. A Mutual Information (MI) of ? 3 and a minimum frequency of < 20 occurrences was applied to ensure statistical significance. Semantic preferences were further examined using the UCREL Semantic Analysis System to categorize collocates into semantic domains. The findings revealed that adapt and modify shared the highest number of noun collocates, indicating a strong synonymous relationship, whereas modify and adjust showed the weakest overlap. The adverbial patterns confirmed that adapt aligned closely with adjust in contexts denoting gradual or behavioral change, while modify was associated with scientific or technical alterations. These results demonstrated that the three verbs cannot be used interchangeably in all contexts. In general, this study provides valuable pedagogical implications for English language teaching and learning, emphasizing the importance of corpus-informed approaches in differentiating near synonyms.